Sexual harassment among employees and students at a large Swedish university: who are exposed, to what, by whom and where - a cross-sectional prevalence study - A. Agardh; G. Priebe; M. Emmelin; J. Palmieri; U. Andersson; P-O Östergren (BMC, 2022)
Abstract Background Sexual harassment (SH) in the workplace is prevalent and associated with poor health. Universities are large workplaces with complex formal and informal power relations, which may influence the prevalence of SH. Although employees and students share the university context, few studies on SH have included both groups. The overall aim of the study was to investigate SH among employees and students at a large Swedish public university regarding types of harassment, prevalence in different groups, characteristics of the perpetrators, and the circumstances in which it occurs. Methods A cross-sectional analysis was performed, based on a web-based survey with 120 items that was sent out to all staff, including PhD students (N = 8,238) and students (N = 30,244) in November 2019. The response rate was 33% for staff and 32% for students. Exposure to SH was defined as having experienced at least one of ten defined SH behaviors during their work or studies. Results Among women, 24.5% of staff and 26.8% of students reported having been exposed to SH. The corresponding figures were 7.0% and 11.3% for male staff and students and 33.3% and 29.4% for non-binary individuals among staff and students. Unwelcome comments, suggestive looks or gestures, and 'inadvertent' brushing or touching were the three most common forms of reported harassment, both among staff and students. Attempted or completed rape had been experienced by 2.1% of female and 0.6% of male students. Male and female perpetrators were reported by about 80% and 15%, respectively, of exposed participants. Among staff most reported events occurred during the everyday operation of the university, while among students the majority of the events took place during social events linked to student life. When exposed to a perpetrator from the same group (staff or students), women reported more often being in a subordinate power position in relation to the perpetrator. Conclusions The results indicate that sexual harassment is common in the university context, and interventions and case management routines of events should consider power relations between victim and perpetrator, as well as the various contexts within which sexual harassment takes place.